2002
DOI: 10.1614/0890-037x(2002)016[0659:gtmcig]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Glufosinate Tank-Mix Combinations in Glufosinate-Resistant Rice (Oryza sativa)1

Abstract: At 14 d after treatment (DAT), glufosinate at 0.42 kg ai/ha controlled barnyardgrass and broadleaf signalgrass 85 and 86%, respectively. Antagonism occurred for barnyardgrass control with all mixtures of glufosinate at 0.42 kg/ha. At 14 DAT, no herbicide was superior to glufosinate at either rate when applied in mixture for the control of broadleaf signalgrass. Rice flatsedge control 7 DAT was 68 and 82% with glufosinate at 0.42 and 0.84 kg/ha alone, respectively. The addition of propanil and triclopyr enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Combinations of two or more herbicides provide an opportunity for an interaction to occur that could be greater than (synergistic) or less than (antagonistic) an expected response (Colby 1967; Fish et al 2015, 2016). For example, Lanclos et al (2002) reported an antagonistic response when glufosinate was mixed with bensulfuron or triclopyr, resulting in reduced barnyardgrass control. Conversely, a synergistic effect was observed for barnyardgrass control when tank-mixing propanil with quinclorac, thiobencarb, or pendimethalin (Baltazar and Smith 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Combinations of two or more herbicides provide an opportunity for an interaction to occur that could be greater than (synergistic) or less than (antagonistic) an expected response (Colby 1967; Fish et al 2015, 2016). For example, Lanclos et al (2002) reported an antagonistic response when glufosinate was mixed with bensulfuron or triclopyr, resulting in reduced barnyardgrass control. Conversely, a synergistic effect was observed for barnyardgrass control when tank-mixing propanil with quinclorac, thiobencarb, or pendimethalin (Baltazar and Smith 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Glyphosate controls barnyardgrass as well as knotgrass, a perennial grass with similar growing characteristics to creeping rivergrass (De Datta et al 1979;Norris et al 2001). Glufosinate controls barnyardgrass, genetically similar to creeping rivergrass (Lanclos et al 2002). Glyphosate and glufosinate are not currently labeled for rice; however, burndown prior to planting mighty be an option.…”
Section: Resultsmentioning
confidence: 99%
“…Transgene stacks with glufosinate and PPO (protoporphyrinogen IX oxidase)‐inhibiting herbicides would not be at risk of resistance evolving in weeds if the above‐listed criteria were observed. However, there is the possibility that combining contact herbicides may present a problem, as the efficacy of one or both of the herbicides may be compromised by antagonistic interference . One caveat is that some A. tuberculatus and A. palmeri populations have already evolved resistance to the PPO‐inhibiting herbicides, and resistant populations are evolving with increasing frequency .…”
Section: Evaluation Of Gene Stacks Based On the Above Criteriamentioning
confidence: 99%